Hierarki Kebutuhan Tokoh Handa Seishuu Dalam Live Action Anime “Barakamon”: Psikoanalisis Abraham Maslow - Falikha, Salwa; Oemiati, Sri (KIRYOKU, 2024)
The goal of this study is do describe how Handa Seishuu, the main character, employs hierarchical needs elements. The authors’s research approach is descriptive qualitative. The purpose of this study is to analyze Handa Seishuu's character's hierarchy of wants using Abraham Maslow's psychology theory. This study's data comes in the form of scenes and dialogue lines connected to the research issue. The results showed that Handa Seishuu's character fulfills the stages of hierarchical needs according to Abraham Maslow's theory: 1) psychological needs in the form of food and shelter, 2) Security needs in the form of meeting people who live on Goto Island, 3) The need to be owned and loved in the form of affection from friends, 4) Self-esteem needs in the form of appreciation or praise from others, 5) Self-actualization needs in the form of trying to develop potential.